2020
DOI: 10.1103/physrevd.101.026004
|View full text |Cite
|
Sign up to set email alerts
|

Complete form factors in Yang-Mills from unitarity and spinor helicity in six dimensions

Abstract: We present a systematic procedure to compute complete, analytic form factors of gauge-invariant operators at loop level in pure Yang-Mills. We consider applications to operators of the form TrF n where F is the gluon field strength. Our approach is based on an extension to form factors of the dimensional reconstruction technique, in conjunction with the six-dimensional spinor-helicity formalism and generalized unitarity. For form factors this technique requires the introduction of additional scalar operators, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Possible operators include those studied in refs. [33,102,[136][137][138][139][140][141][142][143][144][145][146]. In particular, in the case of the two-loop three-point form factor for tr(F 3 ) it has been shown that the next-to-leading order contribution to the Higgs amplitude remainder in the heavy-top limit of QCD shares its maximally transcendental part with its counterpart in N = 4 sYM theory [122,[147][148][149].…”
Section: Discussionmentioning
confidence: 99%
“…Possible operators include those studied in refs. [33,102,[136][137][138][139][140][141][142][143][144][145][146]. In particular, in the case of the two-loop three-point form factor for tr(F 3 ) it has been shown that the next-to-leading order contribution to the Higgs amplitude remainder in the heavy-top limit of QCD shares its maximally transcendental part with its counterpart in N = 4 sYM theory [122,[147][148][149].…”
Section: Discussionmentioning
confidence: 99%
“…We will systematically ignore such contact terms at four points, except for the four-scalar contact term (corresponding in the Lagrangian formalism to the λφ 4 interaction). Indeed, such terms are usually computed through d-dimensional generalised unitarity techniques as one-loop finite rational terms [114,117,[149][150][151][152][153][154], hence they must be vanishing at tree-level. 16 In particular, in the case of the four-scalar amplitude we will add to the factorisable part a contact term whose kinematic dependence is trivial:…”
Section: Jhep11(2021)221mentioning
confidence: 99%
“…Among the various results, they satisfy BCFW recursion relations [57], also at loop level [173], can be computed using (generalised) unitarity, and are invariant under a form of dual conformal symmetry [174], which is broken at loop level. Analytic non-supersymmetric form factors were recently computed at one loop [175] using dimensional reconstruction [176][177][178][179].…”
Section: General Propertiesmentioning
confidence: 99%